Hyperactivity and Hypermotivation Associated With Increased Striatal mGluR1 Signaling in a Shank2 Rat Model of Autism - Modi, Meera E.; Brooks, Julie M.; Guilmette, Edward R.; Beyna, Mercedes; Graf, Radka; Reim, Dominik; Schmeisser, Michael J.; Boeckers, Tobias M.; O’Donnell, Patricio; Buhl, Derek L. (Frontiers in Molecular Neuroscience, 2018)
Mutations in the SHANK family of genes have been consistently identified in genetic and genomic screens of autism spectrum disorder (ASD). The functional overlap of SHANK with several other ASD-associated genes suggests synaptic dysfunction as a convergent mechanism of pathophysiology in ASD. Although many ASD-related mutations result in alterations to synaptic function, the nature of those dysfunctions and the consequential behavioral manifestations are highly variable when expressed in genetic mouse models. To investigate the phylogenetic conservation of phenotypes resultant of Shank2 loss-of-function in a translationally relevant animal model, we generated and characterized a novel transgenic rat with a targeted mutation of the Shank2 gene, enabling an evaluation of gene-associated phenotypes, the elucidation of complex behavioral phenotypes, and the characterization of potential translational biomarkers. The Shank2 loss-of-function mutation resulted in a notable phenotype of hyperactivity encompassing hypermotivation, increased locomotion, and repetitive behaviors. Mutant rats also expressed deficits in social behavior throughout development and in the acquisition of operant tasks. The hyperactive phenotype was associated with an upregulation of mGluR1 expression, increased dendritic branching, and enhanced long-term depression in the striatum but opposing morphological and cellular alterations in the hippocampus. Administration of the mGluR1 antagonist JNJ16259685 selectively normalized the expression of striatally mediated repetitive behaviors and physiology but had no effect on social deficits. Finally, Shank2 mutant animals also exhibited alterations in electroencephalography (EEG) spectral power and event-related potentials, which may serve as translatable EEG biomarkers of synaptopathic alterations. Our results show a novel hypermotivation phenotype that is unique to the rat model of Shank2 dysfunction, in addition to the traditional hyperactive and repetitive behaviors observed in mouse models. The hypermotivated and hyperactive phenotype is associated with striatal dysfunction, which should be explored further as a targetable mechanism for impairment in ASD.